How New Zealand migrants fare in Australia: what explains their wealth gap? - Doan, Tinh; Holmes, Mark; Ha, Van; Tran, Tuyen (My University, 2022)
This paper investigates net wealth of the New Zealand-born (NZ-born) migrants relative to that of Australia-born, and other migrants in Australia. We consider how the free cross-border labour movement between Australia and New Zealand affects the wealth accumulating behaviour of NZ migrants. Our findings indicate that the NZ-born have lower net wealth than both the Australia-born and other migrants. The net wealth differential between the NZ- and Australia-born is mainly explained by the structure effect than from the composition effect (due to differences in observed characteristics, which are similar in both groups). In contrast, comparing with other migrants, the contribution of observed characteristics such as education, age, household composition, weekly wage, and long-term health conditions dominates the overall NZ-born’s net wealth differentials.
New Zealand Economic Papers
Keywords: Income, wealth and finances; Labour market; Migration and settlement